ANALISIS PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN UMUM JAMINAN KREDIT INDONESIA - NI PUTU RISHNA KUMALA SAPUTRI; KASIANI KASIANI; COKORDA GEDE PUTRA YUDISTIRA; I MADE WIDIANTARA (GANEC SWARA, 2021)
This study aims to determine whether the recruitment and selection effect on employee performance both in partially and simultaneously at the Indonesian Credit Guarantee Company Denpasar Branch Office. This research was conducted for 6 months, starting from July to December 2019. The data were collected through a questionnaire method. The number of respondents in this study were 30 employees. The research method that used is quantitative descriptive, while the research tool used descriptive analysis and multiple regression analysis with the help of the IBM SPSS 21 program. The study results showed that the recruitment variable (X1) did not have a significant effect on employee performance because the sig value> 0.05 which is 0.450. Selection (X2) has a significant effect on employee performance where the value of sig <0.05 which is 0.41. The partial test results showed that the selection variable has the highest beta coefficient of 0.513, so it can be concluded that the selection variable has a dominant influence on employee performance. Simultaneously, the recruitment and selection variables have a positive and significant effect on the performance of employees at the Indonesian General Credit Guarantee Company Denpasar Branch Office with the acquisition of a coefficient of determination in 45% and a difference in 55% which is influenced by factors or other variables that are not present in this study.